2020
DOI: 10.1002/etc.4862
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Biota Accumulation Due to Contamination of Sediments by Storm Water Heavy Metals

Abstract: Evaluating sediment recontamination due to storm water discharges is important when evaluating the long-term effectiveness of sediment remediation efforts at reducing biological impacts. The bioaccumulation of the heavy metals zinc, nickel, copper, cadmium, mercury, and lead and the metalloid arsenic in a clam (Macoma nasuta) was studied in surficial sediments before and after storm water inputs from Paleta Creek, California, USA, during wet seasons in 2015 to 2016 and 2016 to 2017. The bioaccumulation was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…The strongest correlations were detected between the passive sampler accumulation and organism bioaccumulation, with much weaker relationships found for comparisons between organism and sediment concentrations. Finally, Drygiannaki et al (2020) also reported stronger correlations between bioaccumulation of several toxic metals by clams ( Macoma nasuta ) and porewater concentrations based on DGTs compared with poor correlations with bulk sediment concentrations collected from a creek in California. While these examples demonstrate the usefulness of passive sampling as a surrogate for bioaccumulation, there is a special form of bioaccumulation, biomagnification, which results in exposure conditions that passive sampling may not be able to accurately capture during a conventional deployment.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest correlations were detected between the passive sampler accumulation and organism bioaccumulation, with much weaker relationships found for comparisons between organism and sediment concentrations. Finally, Drygiannaki et al (2020) also reported stronger correlations between bioaccumulation of several toxic metals by clams ( Macoma nasuta ) and porewater concentrations based on DGTs compared with poor correlations with bulk sediment concentrations collected from a creek in California. While these examples demonstrate the usefulness of passive sampling as a surrogate for bioaccumulation, there is a special form of bioaccumulation, biomagnification, which results in exposure conditions that passive sampling may not be able to accurately capture during a conventional deployment.…”
Section: Introductionmentioning
confidence: 99%
“…The Jinduicheng molybdenite ore is the second largest Mo deposit in Asia [8]. Longterm open-pit mining, accumulation and transportation of ore, and rain erosion can lead to a migration of main and trace elements from ore to aquatic sediment and soil [9][10][11][12][13]. The magmatic rocks in the Jinduicheng mining area are well developed, mainly acidic rocks like those of the granite porphyry series.…”
Section: Introductionmentioning
confidence: 99%